Screen printed TiO2 film: A candidate for photovoltaic applications - Rayees Ahmad Zargar; Navjyoti Boora; Malik Mubasher Hassan; Aslam Khan; Aurangzeb Khurram Hafiz (Materials Research Express, 2020)
In this paper we report synthesis and analysis of low cost screen printed coating of TiO _2 in the form of thick film fabricated on glass substrate followed by annealing at 350 °C. The film has been characterized by x-ray diffraction (XRD), Scanning electron microscope (SEM) with energy dispersive x-ray (EDX), UV-visible and Fourier-transform infrared(FTIR) spectroscopy and current-voltage (I-V) measurement via two probe. The XRD analysis showed that the prepared thick film has crystal structure of anatase phase with preferred orientation of (1 0 1)plane. The SEM image identified porous nature of film while EDX spectra revealed the presence of titanium and oxygen atoms in the film. The FTIR spectrum displayed the strong presence of TiO _2 . DC electrical conductivity measurements revealed that electrical conductivity increases on increasing temperature which confirms semiconducting behaviour.